Towards 4-dimensional atomic force spectroscopy using the spectral inversion method - Williams, Jeffrey C.; Solares, Santiago D. (Beilstein Journal of Nanotechnology, 2013)
We introduce a novel and potentially powerful, yet relatively simple extension of the spectral inversion method, which offers the possibility of carrying out 4-dimensional (4D) atomic force spectroscopy. With the extended spectral inversion method it is theoretically possible to measure the tip–sample forces as a function of the three Cartesian coordinates in the scanning volume (x, y and z) and the vertical velocity of the tip, through a single 2-dimensional (2D) surface scan. Although signal-to-noise ratio limitations can currently prevent the accurate experimental implementation of the 4D method, and the extraction of rate-dependent material properties from the force maps is a formidable challenge, the spectral inversion method is a promising approach due to its dynamic nature, robustness, relative simplicity and previous successes.
Keywords: atomic force microscopy; spectral inversion; spectroscopy; torsional harmonic cantilever; viscoelasticity